Lost and found: the rediscovery of the lost fern species Asplenium achalense (Aspleniaceae) and assessment of its conservation status - Marcelo Arana; Evangelina Natale; Antonia Oggero (Oryx)
The fern of Achala Asplenium achalense Hieron. (Aspleniaceae), endemic to north-west and central Argentina, was formerly considered a lost species. We describe its rediscovery in August 2022 in the Yungas biogeographical province, compile a map of all historical and current records of the species, and propose an IUCN Red List status. We estimated the fern of Achala's range using the area of occupancy of the rediscovered population, calculated as 4 km2 because it is located in a single 2 × 2 km grid square. The extent of occurrence cannot be calculated because only a single living population is known. These data suggest a provisional categorization of the fern of Achala as Critically Endangered based on criteria B2ab(i,ii,iii,iv,v). The species should be considered Regionally Extinct in its locus classicus in Comechingones biogeographical province. We recommend securing the conservation of the single known population (which does not lie within a conservation unit), further surveys for the species in the five protected areas where it was recorded historically, and restoration of the species in the wild. To support the latter, we are cultivating spores and gametophytes of the fern of Achala, in collaboration with colleagues from the National University of La Plata.